Pemanfaatan nilai kearifan lokal siri’ na pesse’ dalam pencegahan stigma remaja ODHIV: A systematic literature review - Jamil, Bidasari; Zamli, Zamli (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Stigma against adolescents living with Human Immunodeficiency Virus (HIV) is a multidimensional problem that significantly impacts mental health, social relationships, and treatment adherence. This stigma is formed through a social construction process influenced by cultural values ​​of honor and shame, and reinforced by the dynamics of interactions on social media. Purpose: To review various literature on the use of local wisdom values ​​(siri' na pesse') in preventing stigma among adolescents living with HIV. Method: A systematic literature review (SLR) of national and international journal articles was conducted based on topic suitability, use of a theoretical framework, cultural relevance, and validity of the DOI. The data extraction process was conducted using a matrix that included study characteristics, research methods, theoretical foundations, forms of stigma, the role of cultural values, types of interventions, and their relevance to local wisdom values. Results: People living with HIV experience stigma in the form of internalized, embodied, perceived, and anticipated stigma. This stigma contributes to mental health disorders, decreased social relationships, and non-adherence to treatment. Cultural values ​​regarding honor and shame, as well as the use of social media, play a role in shaping and reproducing stigma across various communities. Identified interventions include family-based, school-based, community-based, culture-based, and digital approaches. Conclusion: The findings of this study provide a conceptual foundation for developing an intervention model to prevent stigma against people living with HIV (PLHIV) based on Siri' na Pesse' cultural values, specifically in the local context of Palopo City. Suggestion: Longitudinal studies are needed to evaluate the effectiveness of culture-based interventions in reducing long-term stigma. Future research should also explore the perspectives of health workers and teachers as key actors in shaping adolescent social norms. Keywords: Adolescents; Local Wisdom Values; People Living with Human Immunodeficiency Virus (PLHIV). Pendahuluan: Stigma terhadap remaja Orang Dengan Human Immunodeficiency Virus (ODHIV) merupakan permasalahan multidimensional yang berdampak signifikan terhadap kesehatan mental, relasi sosial, serta kepatuhan pengobatan. Stigma tersebut terbentuk melalui proses konstruksi sosial yang dipengaruhi oleh nilai budaya kehormatan dan rasa malu, serta diperkuat oleh dinamika interaksi di media sosial. Tujuan: Untuk mengkaji berbagai literatur tentang pemanfaatan nilai kearifan lokal siri’ na pesse’ dalam pencegahan stigma remaja ODHIV. Metode: Penelitian systematic literature review (SLR) terhadap artikel jurnal nasional dan internasional yang diseleksi berdasarkan kesesuaian topik, penggunaan kerangka teori, relevansi budaya, serta validitas DOI. Proses ekstraksi data dilakukan menggunakan matriks yang mencakup karakteristik studi, metode penelitian, landasan teori, bentuk stigma, peran nilai budaya, jenis intervensi, dan relevansinya dengan nilai kearifan lokal. Hasil: Menunjukkan bahwa ODHIV mengalami stigma dalam bentuk internal, enacted, perceived, dan anticipated stigma. Stigma tersebut berkontribusi terhadap gangguan kesehatan mental, penurunan kualitas hubungan sosial, serta ketidakpatuhan terhadap pengobatan. Nilai budaya kehormatan dan rasa malu, serta penggunaan media sosial, berperan dalam membentuk dan mereproduksi stigma dalam berbagai komunitas. Intervensi yang diidentifikasi meliputi pendekatan berbasis keluarga, sekolah, komunitas, budaya, dan digital. Simpulan: Temuan penelitian ini memberikan landasan konseptual bagi pengembangan model intervensi pencegahan stigma ODHIV berbasis nilai budaya Siri’ na Pesse’, khususnya dalam konteks lokal Kota Palopo. Saran: Diperlukan studi longitudinal untuk mengevaluasi efektivitas intervensi berbasis budaya dalam mengurangi stigma jangka panjang. Penelitian selanjutnya juga perlu menggali perspektif tenaga kesehatan dan guru sebagai aktor penting dalam membentuk norma sosial remaja. Kata Kunci: Nilai Kearifan Lokal; Orang Dengan Human Immunodeficiency Virus (ODHIV); Remaja.